Anxiolytic effects of ACE inhibitory peptides on the behavior of rats in an elevated plus-maze. Issue 1 (3rd November 2015) - Yu, Zhipeng; Zhao, Wenzhu; Ding, Long; Yu, Yiding; Liu, Jingbo
Abstract : Three novel egg white-derived peptides were demonstrated to display in vitro activities against the angiotensin converting enzyme (ACE). Abstract : Three novel egg white-derived peptides were demonstrated to display in vitro activities against the angiotensin converting enzyme (ACE). A further study was conducted to assess their anxiolytic-like effects upon spontaneously hypertensive rats (SHRs) after an oral administration of the peptides, which showed the same behavioral performance as that using an elevated plus maze (EPM). In the EPM experiment, the behavioral effects of peptides TNGIIR, RVPSL, and QIGLF were investigated at doses ranging from 5 to 50 mg kg −1, with records of the number of entries by the rats into the open arms, the time the rats spent in the open arms, and the total amount of entries into the open + closed arms. The results showed that the peptides TNGIIR and RVPSL, in a range of 5–50 mg kg −1, exerted an anxiolytic effect on the SHRs. These results suggested that the egg white derived peptides TNGIIR and RVPSL could be considered as possible functional food or food ingredients due to their in vivo anti-stress and anti-anxiety effects on the SHRs.